The renewable energy sources as a lever of sustainable development - Maria Tsiouni; Dafni Petkou; Alexandra Pavloudi (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2023)
Purpose: The aim of this paper is to examine investors' economic and social profiles in renewable energy sources with the help of widely used investment rating indicators, such as Net Present Value, Internal Grade of Performance and Profitability Index. Design/methodology/approach: The study used an empirical research, gathering economic data from investments in renewable energy sources in the Regional Units of Thessaloniki, Imathia and Pella. Data was collected through a structured questionnaire, administered with personal interviews with investors, by applying a simple random sampling method through a population-total number of investors retrieved from the Ministry of Environment, Energy, and Climate Change records. Findings: The results demonstrate that investments in renewable energy projects are sustainable and highly efficient on a case-by-case basis. The main criterion for accepting an investment element in a specific renewable energy technology application is the calculation of the Internal Rate of Return. The optimal investment pertains to photovoltaic system installations. Among the investments, hydroelectric and wind investments are also enticing. Investments in wind energy have the highest net present value, followed by investments in photovoltaic and hydroelectric systems. Concerning the profitability index, it is observed that investments in photovoltaic systems have a higher profitability index, followed by investments in wind and hydroelectric systems. As far as social characteristics are concerned, the majority of investors, regardless of their profession, invest in photovoltaics. Freelancers predominantly invest in wind energy projects, while employees mainly invest in hydroelectric projects. Research limitations/implications: The main limitation of the survey is related to the sample, which consisted of investors from three regional areas of Greece. A future study may be conducted to a larger sample, from all Greek regional units and examine possible differences in the results related to geographical area and profile of the investors. Originality/value: From the literature review, it is found that there is a lack of a comprehensive scientific method for evaluating the optimal investment choice in the renewable energy sector, leaving potential investors without a reliable framework for assessment of investment proposals. The current study can serve as a tool for investors in the renewable energy sector, assessing whether an investment yields financial gains compared to the capital allocated and therefore providing a tool to investors to know in advance the benefit of their potential investment.
Keywords: G11; M21; O13; Q01; Q49; Q50; 330; Renewable energy; environmental policy; Net Present Value; Internal Grade of Performance; Profitability Index